Implications of the topological properties of networks in the dynamics in marketing, competition, and framing analysis - Legara, Erika Fille Tupas; Monterola, Christopher P.; Saloma, Caesar A. (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2011)
The science of networks has emerged to be a leading approach in probing complex systems signatures inherent in both nature and society. One of the many compelling issues that interest contemporary researchers across disciplines is capturing accurately the systems dynamics and evolution from a compendium of data. This dissertation applies the general concepts and methods of complex networks to four socio-economic systems/issues. Essentially, analyses are done using the framework of network theory.
Thesis (Ph.D. - Physics) --University of the Philippines Diliman
Keywords: System analysis; Electric network topology